Gust-induced flow perturbations on circular cylinder: Investigating the effects and characteristics - Sudarsan Gajula; Nilotpala Bej; Atal Bihari Harichandan (International Journal of Thermofluids, 2024)
This paper delves into the fascinating realm of gust flow past a circular cylinder, unveiling the dynamic interactions and key features that influence the system's behavior. In this study, ANSYS Fluent is used to perform numerical simulations based on finite volume method. The aim is to investigate the temporal evolution of the aerodynamic forces at different Reynolds numbers (Re) at different gust frequencies. In this study, gusts are generated by harmonically changing the direction of the inlet velocity at different frequencies. Unlike uniform flow, vortices are shed simultaneously from the upper and lower surface of cylinder, sometimes with equal strengths and sometimes with varying strengths depending upon the gust frequency. Cl, Cd and Strouhal number values increase with gust frequency corresponding to any Reynolds number. However, the values remain less than no-gust case under similar flow situations. Fast Fourier transform analysis has been used to examine the energy spectrum and kinetic energy contours of vorticity and turbulence to gain further insight into fluid physics. The results of this study provide valuable insight into the physics of gust flow and circular cylinders.